An Efficient One-Pot Synthesis of 1,4-Oxathiane and 1,4-Thiomorpholine Derivatives - Samzadeh-Kermani, Alireza (Synlett, 2014)
An efficient one-pot reaction of nitromethane, isothiocyanates, and three-membered heterocyclic rings (oxiranes and aziridines) for the synthesis of 1,4-oxathiane and 1,4-thiomorpholine derivatives is reported. This procedure is carried out in the presence of K2CO3 in DMF at 60 °C.
Keywords: cyclization; epoxides; heterocycles; multicomponent reaction; ring opening